Cosmopolitanism and translation investigations into the experience of the foreign - Bielsa, Esperança 1971- (Translation theories explored, 2016)
In Cosmopolitanism and Translation, Esperança Bielsa does just that by focussing on the lived experience of the cosmopolitan stranger, whether a traveller, migrant, refugee or homecomer. With reference to world literature, social theory and foreign news, she argues that this key figure of modernity has a central relevance in the cosmopolitanism debate